The Development of Mathematics Learning Module Based of Character - Alfiyan Ghifari Akbar; Iesyah Rodliyah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to describe the results of the development of a character-based mathematics education module. This study uses a research model developed by Thiagarajan (1974) which is more popularly known as 4D (define, design, develop, dessiminate). However, due to the covid-19 virus pandemic, the research only reached the development stage. At the develop stage, a validation test and a readability test were carried out, for the module readability test was carried out by a small group test totaling six students. The results of this study indicate that the module has met the valid criteria. based on the results of the media validator score showed 68.3% with valid criteria. and the material validator shows a score of 8.9% with valid criteria, and the average score of the two validators is 76.1% which means that the module has been used to be used.   Keywords: learning module, character, triangle and quadrilateral